Exploring the Dynamics of Global Liquidity - Chen, Sally (IMF Working Papers; Working Paper ;, 2012)
This paper explores the concept of global liquidity, its measurement and macro-financial importance. We construct two sets of indicators for global liquidity: a quantity series distinguishing between core and noncore liabilities of financial intermediatires and a corresponding price series. Using price and quantity indicators simultaneously, it is possible to distinguish between shocks to the supply and demand for global liquidity, and isolate their impact on the economy. Our results confirm that global liquidity conditions matter for economic and financial stability, and points to indicators whose regular monitoring could be valuable to policymakers.a.